2020
DOI: 10.1117/1.jei.29.4.041011
|View full text |Cite
|
Sign up to set email alerts
|

Calibration algorithms for polarization filter array camera: survey and evaluation

Abstract: A polarization filter array (PFA) camera is an imaging device capable of analyzing the polarization state of light in a snapshot manner. These cameras exhibit spatial variations, i.e., nonuniformity, in their response due to optical imperfections introduced during the nanofabrication process. Calibration is done by computational imaging algorithms to correct the data for radiometric and polarimetric errors. We reviewed existing calibration methods and applied them using a practical optical acquisition setup an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…2. It is grounded on the super-pixel calibration method detailed in [11], [23], which is a well-established method in the literature. The originality of our calibration algorithm is that no information about the input light polarization state is required.…”
Section: Calibration Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2. It is grounded on the super-pixel calibration method detailed in [11], [23], which is a well-established method in the literature. The originality of our calibration algorithm is that no information about the input light polarization state is required.…”
Section: Calibration Methodsmentioning
confidence: 99%
“…( 10) constitutes the super-pixel calibration equation, and it can be solved for A if the polarization states of the N input calibration light samples are known . These states corresponds to the N columns of the matrix: (11) where S 0n is the intensity of the n th calibration light sample, ρ n is its degree of linear polarization (DoLP), and α n is its angle of linear polarization (AoLP), for n = 1, ..., N . These parameters can be obtained with high accuracy but at the expense of a complex laboratory set-up and time consuming experiments.…”
Section: A Description Of the Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Using the polarimetric characterization in Ref. 42, we found that the polarization measurement is near to ideal for these sensors (very high extinction ratios of the micropolarizers), so there is no need to calibrate polarimetrically. )…”
Section: Calibrationmentioning
confidence: 99%
“…Number of acquisitions needed, along with the selection of the angle of analysis have been previously discussed by Tyo et al 14 Angles could differ from the ones used to calculate the Stokes vector in Eq. 2, and polarization elements do not need to be ideal, thus the polarimeter has to be polarimetrically calibrated [15][16][17] by estimating W. Afterward, S can be deduced by an inversion procedure, and polarization properties of light beams like Angle Of Linear Polarization (AOLP), Degree Of Polarization (DOP), or ellipticity, can be derived from the Stokes vector.…”
Section: Polarization Imaging Modelmentioning
confidence: 99%